Instructional Resources of Teacher Education Programs in the Philippine Higher Education Institution Towards Quality Teaching and Learning - Manzano, Jeanno (FKIP Universitas Lampung, 2023)
Instructional Resources of Teacher Education Programs in the Philippine Higher Education Institution towards Quality Teaching and Learning. Objective: Instructional resources play an important function in delivering quality teaching and learning, thus, there is a need for its continuous assessment and improvement in order to meet the diverse needs of the Teacher Education Programs as emphasized in this research paper. Methods: This descriptive study employed quantitative techniques to assess the status of teacher education curricula in terms of instructional resources. Respondents were the graduating students, faculty members, and administrators from the Teacher Education Programs. Finding: In the assessment, it was concluded that the College had satisfactorily provided the instructional resources for the enrichment of students’ skills and capabilities that will better train them as a future teacher. Conclusion: Quality teaching and learning is manifested by a classroom instruction enriched with varied strategies appropriate to the students' needs and capabilities. Physical facilities for athletic and extra-curricular activities were provided and there are laboratories for hands-on training of students. Keywords: teacher education program, instructional resources, physical facilities, curriculum, instruction.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202344